2021
DOI: 10.1152/physiol.00029.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptors in Metabolic Regulation and Diabetes

Abstract: There is an urgent need for developing effective drugs to combat the obesity and Type 2 diabetes mellitus epidemics. The endocannabinoid system plays a major role in energy homeostasis. It comprises the cannabinoid receptors 1 and 2 (CB1 and CB2), endogenous ligands called endocannabinoids and their metabolizing enzymes. Because the CB1 receptor is overactivated in metabolic alterations, pharmacological blockade of the CB1 receptor arose as a promising candidate to treat obesity. However, because of the wide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…This may involve purinergic signaling via G-protein-coupled receptors (GPCRs) activated by adenosine or nucleotides [ 42 , 43 , 44 , 45 ]. Speculatively, endocannabinoids might also influence hepatic glucose metabolism via GPCRs [ 46 ]. Undoubtedly, hitherto unknown exercise-responsive myokines will also be discovered through global mRNA sequencing and secretome and metabolome analysis [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may involve purinergic signaling via G-protein-coupled receptors (GPCRs) activated by adenosine or nucleotides [ 42 , 43 , 44 , 45 ]. Speculatively, endocannabinoids might also influence hepatic glucose metabolism via GPCRs [ 46 ]. Undoubtedly, hitherto unknown exercise-responsive myokines will also be discovered through global mRNA sequencing and secretome and metabolome analysis [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, GPR55, another cannabinoid-sensitive receptor, plays a role in cardiovascular homeostasis and disease by influencing intracellular signaling cascades. Endocannabinoids like AEA and 2-AG act as primary ligands for cannabinoid receptors, modulating physiological and pathological conditions through autocrine and paracrine mechanisms [51][52][53][54][55].…”
Section: Direct Effects On Cardiac Ion Channelsmentioning
confidence: 99%
“…Interestingly, CB1 has been identified within the podocytes, allowing the ECS to be a target for study [53]. It has been well-characterized that the ECS plays a major role in diabetes and metabolic diseases, which in turn brings focus to diabetic nephropathy [56][57][58][59]. In a 2014 study performed by Jourdan et al, high glucose levels were found to affect CB1 activation in podocytes, causing increased Cnr1 expression [54].…”
Section: The Ecs and Chronic Kidney Disease 21 Diabetic Kidney Diseasementioning
confidence: 99%